Development of Desktop Application with Three Dimensional (3D) Pageflip Professional Based on Network Design and Construction Class XI TKJ - Ayu Hidayati; Dedy Irfan; Asrul Huda (Universitas Budi Darma, 2022)
This research and development aims to produce products in the form of E-Modules or electronic modules based on three dimensions (3d) Pageflip Professional in NETWORK DESIGN AND BUILDING Subjects (RBJ) Class XI Computer and Network Engineering (TKJ) at SMK Negeri 2 Padang. After the validity test has been carried out by the experts, the overall assessment of the validator test on the E-Modul or electronic applicationbased on three dimensions (3d) Pageflip Professional in the NETWORK DESIGN AND BUILDING (RBJ) Subject is 89.94%, so that the level of validity can be interpreted as valid. . The results of the overall practicality test assessment of the E-applicationbased on 3d Pageflip Professional in the NETWORK DESIGN AND BUILDING (RBJ) Eye is 89.50%, so that the practicality level can be interpreted as very practical to use. The results of the overall effectiveness test assessment of the effectiveness of the 3d Pageflip Professional-based E-Modul in NETWORK DESIGN AND BUILDING (RBJ) subjects are 90.63%, so that the level of effectiveness can be interpreted as very effective to use.